Drivers and forecasting of carbon emissions with extended LMDI and Bagging models: A case study of China's Bohai Rim region. - Wen Yu; Jianguo Lin; Shusheng Yin (PLoS ONE)
The Bohai Rim region, one of the prominent coastal economic zones in China, has garnered considerable attention regarding its carbon emission characteristics and driving factors. This paper computes the overall carbon emissions within the Bohai Rim by utilizing economic and energy usage data spanning the years 2009to 2021. The results indicate a clear pattern in carbon emissions, which rise at first before experiencing a decline, primarily driven by substantial contributions from the industrial and transportation sectors. The three-layer extended Log Mean Divisia Index (LMDI) decomposition model examines how different driving characteristics affect carbon emissions, including energy composition, industrial framework, and the level of economic advancement. The study finds that despite regional economic growth, carbon emissions are declining overall. In the industrial sector, emissions reduce in large part by optimizing the energy mix and increasing energy efficiency. Similarly, modal shifts and energy efficiency advancements positively impact emission reduction in the transportation sector. Furthermore, trends in carbon emissions are predicted using a bagging ensemble model for the Bohai Rim region's two municipalities and three provinces from 2024 to 2060. This study also examines the carbon emission reduction potential under high-speed, low-speed, and normal socio-economic development scenarios. These findings offer an in-depth insight into carbon emissions in the Bohai Rim of China and provide theoretical foundations and policy suggestions aimed at fostering low-carbon growth in related coastal zones.